Validation of a novel CARTOSEG™ segmentation module software for contrast‐enhanced computed tomography‐guided radiofrequency ablation in patients with atrial fibrillation. Issue 11 (6th October 2017) - Imanli, Hasan; Bhatty, Shaun; Jeudy, Jean; Ghzally, Yousra; Ume, Kiddy; Vunnam, Rama; Itah, Refael; Amit, Mati; Duell, John; See, Vincent; Shorofsky, Stephen; Dickfeld, Timm M.
Abstract: Introduction: Visualization of left atrial (LA) anatomy using image integration modules has been associated with decreased radiation exposure and improved procedural outcome when used for guidance of pulmonary vein isolation (PVI) in atrial fibrillation (AF) ablation. We evaluated the CARTOSEG™ CT Segmentation Module (Biosense Webster, Inc.) that offers a new CT‐specific semiautomatic reconstruction of the atrial endocardium. Methods: The CARTOSEG™ CT Segmentation Module software was assessed prospectively in 80 patients undergoing AF ablation. Using preprocedural contrast‐enhanced computed tomography (CE‐CT), cardiac chambers, coronary sinus (CS), and esophagus were semiautomatically segmented. Segmentation quality was assessed from 1 (poor) to 4 (excellent). The reconstructed structures were registered with the electroanatomic map (EAM). PVI was performed using the registered 3D images. Results: Semiautomatic reconstruction of the heart chambers was successfully performed in all 80 patients with AF. CE‐CT DICOM file import, semiautomatic segmentation of cardiac chambers, esophagus, and CS was performed in 185 ± 105, 18 ± 5, 119 ± 47, and 69 ± 19 seconds, respectively. Average segmentation quality was 3.9 ± 0.2, 3.8 ± 0.3, and 3.8 ± 0.2 for LA, esophagus, and CS, respectively. Registration accuracy between the EAM and CE‐CT‐derived segmentation was 4.2 ± 0.9 mm. Complications consisted of one perforation (1%) which required pericardiocentesis, one increased pericardial effusion treated conservatively (1%), and one early termination of ablation due to thrombus formation on the ablation sheath without TIA/stroke (1%). All targeted PVs (n = 309) were successfully isolated. Conclusions: The novel CT‐ CARTOSEG™ CT Segmentation Module enables a rapid and reliable semiautomatic 3D reconstruction of cardiac chambers and adjacent anatomy, which facilitates successful and safe PVI.